Drought and heat stress mediated activation of lipid signaling in plants: a critical review - Sharma, Parul; Lakra, Nita; Goyal, Alisha; Ahlawat, Yogesh K.; Zaid, Abbu; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2023)
Lipids are a principal component of plasma membrane,acting as a protective barrier between the cell and its surroundings. Abiotic stresses such as drought and temperature induce various lipid-dependent signaling responses, and the membrane lipids respond differently to environmental challenges. Recent studies have revealed that lipids serve as signal mediators forreducing stress responses in plant cells and activating defense systems. Signaling lipids, such as phosphatidic acid, phosphoinositides, sphingolipids, lysophospholipids, oxylipins, and N-acylethanolamines, are generated in response to stress. Membrane lipids are essential for maintaining the lamellar stack of chloroplasts and stabilizing chloroplast membranes under stress. However, the effects of lipid signaling targets in plants are not fully understood. This review focuses on the synthesis of various signaling lipids and their roles in abiotic stress tolerance responses, providing an essential perspective for further investigation into the interactions between plant lipids and abiotic stress.